The Valuation and Hedging of Variable Rate Savings Account - Frank de Jong; Jacco Wielhouwer (Tinbergen Institute, 2001)
Variable rate savings accounts have two main features. The client rate is variable and deposits can be invested and withdrawn at any time. However, customer behaviour is not fully rational and actions are often performed with a delay. This paper focusses on measuring the interest rate risk of variable rate savings accounts on a value basis (duration) and on the problem how to hedgethese accounts. In order to model the embedded options and the customer behaviour we implement a partial adjustment specification. The interest rate policy of the bank is described in an error-correction model.
Keywords: C33; E43; 330; Term structure; duration; uncertain cash flow; variable rates of return; Einlagengeschäft; Zinsstruktur; Hedging; Einlagensicherung; Theorie